Apartments ownership and maintenance - Ahmadnia, Behzad (2010)
In Malaysia, apart from the low-rise development, the high rise apartment buildings are also in demand. However, before the construction of the apartment can begin, the developer will need to apply and obtain approval for the strata title. This process is lengthy and the developer ignores the requirements and proceeds with the development. The objectives of this study is to study the process of the application of the strata title and its legal implication, to identify the amount of management fees, the procurement method and the respond and repair time taken by the maintenance department and the level of residents’ satisfaction regarding the maintenance of the apartment. The study is carried out around Johor Bahru district. The study is carried out using questionnaires and interviews. A total of 150 questionnaires were distributed to the residents of the apartments and a total of 92 questionnaires were duly answered. Interviews were also conducted with the apartment management manager. The data is analyzed using Average Index and statistical analysis. From the study it is found that the process of applying for the strata title is lengthy and there are loop holes regarding the legal aspects. The amount of management fees paid by the residents is between RM0.10/ft2 and RM0.25/ft2. The type of procurement commonly used is by quotation. The overall level of satisfaction from the residents’ is ‘unsatisfactory’.